2022
DOI: 10.3390/su14169807
|View full text |Cite
|
Sign up to set email alerts
|

Internal Temperature Variation on Spontaneous Combustion of Coal Gangue Dumps under the Action of a Heat Pipe: Case Study on Yinying Coal Mine in China

Abstract: Coal gangue spontaneous combustion is a serious catastrophe associated with mining activities. Generally, the areas of coal gangue spontaneous combustion are regions of tremendous heat accumulation. Mastering the regularity of deep temperature distribution and eliminating internal heat is an effective method to control spontaneous combustion. In this study, using self-developed heat pipe (HP) and intelligent cloud monitoring software, three sets of single pipe experiments were conducted in different temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The results showed that HPs can effectively reduce the temperature of the coal gangue dump and control the spread of the high-temperature area. Zhao [29] found that HPs make the temperature distribution in the coal gangue dump more uneven, accelerating the heat dissipation rate. Meng [27] studied the variation law of the temperature field in coal piles under the action of HP and found the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that HPs can effectively reduce the temperature of the coal gangue dump and control the spread of the high-temperature area. Zhao [29] found that HPs make the temperature distribution in the coal gangue dump more uneven, accelerating the heat dissipation rate. Meng [27] studied the variation law of the temperature field in coal piles under the action of HP and found the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Sun Meihua [28] established a mathematical model for the transfer of heat and cooling of coal piles under the action of HPs, exploring the effects of HP insertion depth and angle on the internal temperature field of coal piles. Zhao Na et al [29] conducted an HP test on the coal gangue dump in Yinying, exploring the temperature field distribution at different depths of the coal gangue dump. Zhao Bolin et al [30] analyzed the effect of fin spacing on the heat transfer performance of heat pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term accumulation of gangue can result in internal spontaneous combustion and an increase in the accumulated temperature. This, in turn, leads to a higher concentration of toxic and hazardous gases, such as nitrogen oxides and sulfur oxides, in the surrounding air, posing a serious threat to the ecological environment [2][3][4]. With its excellent isothermal performance, the gravity heat pipe (GHP) can rapidly transfer the deep-seated accumulated heat to the ground, effectively preventing an increase in the internal temperature of the gangue dump [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining coal inside these hills can release a substantial amount of heat through slow atmospheric oxidation, resulting in high temperatures within the gangue hills. The internal temperatures can range from 573 K to 1473 K, while the surface temperatures can exceed 373 K [6,[11][12][13][14][15], which severely impacts vegetation growth and has the potential to lead to disasters such as explosions [16][17][18][19]. Therefore, it is urgent to address the problem of effective treatment methods for coal gangue hills.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional GHPs, gangue hill GHPs do not have a distinct thermal insulation section. Heat is transferred from the inner part of the gangue hill to the outside through the heat pipes and ultimately dissipated by natural conditions [16].…”
Section: Introductionmentioning
confidence: 99%